Sequence and immunologic conservation of Anaplasma marginale OmpA within strains from Ghana as compared to the predominant OmpA variant - Futse, J.E.; Buami, G.; Kayang, B.B.; Koku, R.; Palmer, G.H.; Graca, T.; Noh, S.M. (Plos One, 2019)
A primary challenge in developing effective vaccines against obligate, intracellular, bacterial tick-borne pathogens that establish persistent infection is the identification of antigens that cross protect against multiple strains. In the case of Anaplasma marginale, the most prevalent tick-borne pathogen of cattle found worldwide, OmpA is an adhesin and thus a promising vaccine candidate. We sequenced ompA from cattle throughout Ghana naturally infected with A. marginale in order to determine the degree of variation in this gene in an area of suspected high genetic diversity. We compared the Ghanaian sequences with those available from N. America, Mexico, Australia and Puerto Rico. When considering only amino acid changes, three unique Ghanaian OmpA variants were identified. In comparison, strains from all other geographic regions, except one, shared a single OmpA variant, Variant 1, which differed from the Ghanaian variants. Next, using recombinant OmpA based on Variant 1, we determined that amino acid differences in OmpA in Ghanaian cattle as compared to OmpA Variant 1 did not alter the binding capacity of antibody directed against OmpA Variant 1, supporting the value of OmpA as a highly conserved vaccine candidate.
Research Article
Keywords: effective vaccines; Anaplasma marginale OmpA; Ghanaian cattle; amino acid